NILAI PENDIDIKAN KARAKTER PADA CERPEN WASKAT KARYA WISRAN HADI - Suhardi, Suhardi; Thahirah, Afifah (Universitas Pendidikan Indonesia, 2018)
AbstractThis research aims to describe the values of educational character in Waskat short story by Wisran Hadi. This research used descriptive method. The source of the data is the short story â€œWaskatâ€ written by Wisran Hadi. The data were collected through reading and understanding of the short story carefully and recording educational character values found in the short story. Data analyses were done using Miles and Hubermanâ€™s model (1992), namely: (1) identifying the short story Waskat as the object of the research, (2) reducing the data, (3) presenting the data, (4) interpreting the data obtained by theory, and (5) making conclusion. The results show that Waskat short story contains character education values, such as: (1) religiosity, (2) honesty, (3) tolerance, (4) discipline, (5) rigor, (6) independence, (7) communicativeness, (8) love of peace, and the value of (9) social care. In addition, this short story also contains sense of humor which entertains the reader.